Key Teacher Attitudes for Sustainable Development of Student Employability by Social Cognitive Career Theory: The Mediating Roles of Self-Efficacy and Problem-Based Learning - Liu, Xiang; Peng, Michael Yao-Ping; Anser, Muhammad Khalid; Chong, Wei-Loong; Lin, Biqu (Frontiers in Psychology, 2020)
Higher education policy and talent training are failing to meet the ever-changing expectations of employers and society in Taiwan, resulting in a gap between university education and employment. This study used social cognitive career theory (SCCT) to explore the relationships among self-efficacy, transformational leadership (TL), student employability (SE), and problem-based learning (PBL) in higher education institutions (HEIs). The analysis of 619 undergraduates from 12 Taiwanese HEIs using structural equation modelling shows significant positive correlations among self-efficacy, PBL, TL, and SE, and PBL and self-efficacy are key mediators. Based on these findings, the researchers propose feasible suggestions for related issues and future research.